Experimental study on sand production and coupling response of silty hydrate reservoir with different contents of fine clay during depressurization - Xiangyu Fang; Dianheng Yang; Fulong Ning; Linjie Wang; Zhichao Liu; Yanjiang Yu; Wenwei Xie; Hongfeng Lu; Yanlong Li; Meng Xu (Petroleum, 2023)
To further understand the characteristics of clay and sand production (hereafter collectively referred to as sand production) and to provide optimization designs of sand control schemes are critical for gas production from clayey silt natural gas hydrate reservoirs in the South China Sea. Thus, gas-water-sand production behavoirs and coupling reservoir subsidence characteristics before, during, and after hydrate dissociation of the clayey silt hydrate reservoirs with different clay contents (5%, 10%, 15%, 20%, 25%, and 30%) have been studied through a self-developed experimental system. The results show that with the increase of clay content, the total mass of sand production first increases and then decreases, and it reaches maximum when the clayey content is 20%. The sand production is the lowest before hydrate dissociation and increases significantly during hydrate dissociation, which mainly occurs in the high-speed gas and water production stage at the beginning of hydrate dissociation. After hydrate dissociation, the sand production decreases significantly. During the whole depressurization process, the clay and free sand particles generally move to the sand outlet due to the fluid driving force and overlying stress extrusion. However, for conditions of high clay contents, those particles fail to pass through the sand control screen and gradually accumulate and block the screen by forming a mud cake, which greatly reduce the permeability of the screen and limite sand production as well as gas and water production. Our research lays a foundation for sand production prediction and sand control scheme selection during gas recovery from clayey silty hydrate reservoirs that greatly need to consider a balance between sand control and gas productivity.